MC4R Gene Polymorphisms Interact With the Urbanized Living Environment on Obesity: Results From the Yi Migrant Study - Wang, Ye; Pan, Li; Wan, Shaoping; Yihuo, Wuli; Yang, Fang; He, Huijing; Li, Zheng; Yong, Zhengping; Shan, Guangliang (Frontiers in Genetics, 2022)
Objectives This study aimed to determine the association of MC4R gene polymorphisms (rs17782313 and rs12970134) and urbanized living environment, and the gene-environment interaction with obesity in Yi people in China. Methods A 1:2 frequency-matched case-control study based on the cross-sectional data was designed. Those with BMI ≥28 kg/m2 were included as the case group. The age- and sex-matched controls were selected from those with BMI<24 kg/m2. Unconditional logistic models were used to determine the association of SNPs with obesity. Additive interaction was evaluated by calculating relative excess risk due to interaction (RERI), attributable proportion due to interaction (AP), and synergy index (SI). Results A total of 322 cases and 643 controls were included. After adjustment, allele C of rs17782313 was significantly associated with obesity (additive model, OR=1.52，95%CI：1.18~1.96) in Yi people. A similar association was found in allele A of rs12970134 (additive model, OR=1.45, 95%CI：1.13~1.89). Yi rural-to-urban migrants were found at 2.59-fold (95%CI: 1.70~3.95) higher odds of obesity than Yi farmers. Additive interactions were found between the two SNPs and rural-to-urban migration (rs17782313: AP=0.65, 95%CI: 0.22~1.09; rs12970134: AP=0.59, 95%CI: 0.02~1.17). Conclusion MC4R gene polymorphisms positively interacted with the urbanized living environment on obesity in Yi people. The effect of MC4R gene on obesity was modified by living environment.